2020
DOI: 10.1101/2020.03.26.008730
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ultrasensitive small molecule fluorogenic probe for human heparanase

Abstract: Heparanase is a critical enzyme involved in the remodeling of the extracellular matrix (ECM), and its elevated expression has been linked with diseases such as cancer and inflammation. The detection of heparanase enzymatic activity holds tremendous value in the study of the cellular microenvironment, and search of molecular therapeutics targeting heparanase, however, assays developed for this enzyme so far have suffered prohibitive drawbacks. Here we present an ultrasensitive fluorogenic small-molecule probe f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…halides) on the aromatic aglycone may promote formation of a more robust -stack with the electron rich ring of Tyr348, with the additional benefit of improving leaving group stability by lowering its pKA. Whilst this manuscript was under preparation, Cui and coworkers reported that difluoro-coumarins are more efficient aglycone leaving groups for HPSE substrates compared to 4MU, essentially confirming the validity of this strategy 35 .…”
Section: Figure 3 a Michaelis Menten Plot For The Hydrolysis Of 1 By Hpse B Competitive Inhibition Of Hpsementioning
confidence: 55%
“…halides) on the aromatic aglycone may promote formation of a more robust -stack with the electron rich ring of Tyr348, with the additional benefit of improving leaving group stability by lowering its pKA. Whilst this manuscript was under preparation, Cui and coworkers reported that difluoro-coumarins are more efficient aglycone leaving groups for HPSE substrates compared to 4MU, essentially confirming the validity of this strategy 35 .…”
Section: Figure 3 a Michaelis Menten Plot For The Hydrolysis Of 1 By Hpse B Competitive Inhibition Of Hpsementioning
confidence: 55%
“…We thus hypothesized that CTLAP emission was attenuated somehow, resulting in reduced background emission (Figure S4B). The emission of some fluorophores is altered by assay pH, often due to the existence of a non‐ or low‐emissive conjugate acid or base form of the fluorophore, [36] but no such effect was observed for AMC (Figure S6).…”
Section: Figurementioning
confidence: 99%
“…A 7-hydroxymethylcoumarin moiety was selected as the donor fluorophore, due to the possibility of functionalization onto a porphyrin scaffold and the excellent spectral overlap with the absorbance spectrum of porphyrin-based compounds ( Figures S1 and S2 ). Additionally, 7-hydroxymethylcoumarin derivatives are also known to be fairly photostable, 41 , 42 including compound 1 ( Figure S3 ), a characteristic that will importantly maximize the observed increase in fluorescence following enzymatic probe cleavage.…”
Section: Introductionmentioning
confidence: 99%